2019
DOI: 10.1021/acs.orglett.9b02273
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reductive Formation of α-Tertiary Ethers from Ketals

Abstract: A general photocatalytic reductive strategy for the construction of unsymmetrical α-tertiary dialkyl ethers is reported. By merging Lewis acid-mediated ketal activation and visible-light photocatalytic reduction, in situ generated α-alkoxy radicals can engage in addition reactions with a variety of olefinic partners. Good reaction efficiency is demonstrated with a range of ketals of aromatic and aliphatic ketones. Extension to acetal substrates is also described, demonstrating the overall synthetic utility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 60 publications
0
16
0
3
Order By: Relevance
“…Previously, our group has reported that the use of bespoke Hantzsch ester reductants can modulate reactivity and in turn increase product yield and/or improve diastereoselectivity in reductive functionalization of imines . A survey of Hantzsch ester reductants (Scheme B, entries 2–4) demonstrated that methyl carboxyphenyl derivative ( HE4 ) led to increased conversion to product (90 %) and to a higher diastereomeric ratio (1.9:1, for further optimization details, see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, our group has reported that the use of bespoke Hantzsch ester reductants can modulate reactivity and in turn increase product yield and/or improve diastereoselectivity in reductive functionalization of imines . A survey of Hantzsch ester reductants (Scheme B, entries 2–4) demonstrated that methyl carboxyphenyl derivative ( HE4 ) led to increased conversion to product (90 %) and to a higher diastereomeric ratio (1.9:1, for further optimization details, see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…FürR eaktionen vom Giese-Typ mit Dha wurden verschiedene Methoden entwickelt, bei denen RAE, [58] Car-bonsäuren, [59] Imine, [60] Ketale, [61] Tr ifluorborate, [62] Alkylhalogenide [63] oder Thioester [64] als Radikalvorläufer verwendet wurden.…”
Section: Racemische Methodenunclassified
“…Several methods have been developed for Giese-type reactions of Dha using RAEs, [58] carboxylic acids, [59] imines, [60] ketals, [61] trifluoroborates, [62] alkyl halides, [63] or thioesters [64] as radical precursors.…”
Section: Racemic Proceduresmentioning
confidence: 99%
“…Dixon and co-workers have recently reported acouple of light-mediated methods for the modification of Dha derivatives using imines [60] and ketals [61] as radical precursors.T he first is athree-component procedure where in situ generated imines are reduced by an Ir-based PC to generate a-amino radicals that add to 12,thereby affording UAAs bearing 1,3diamine motifs (Scheme 20 A). [60] Although the products are generated in good to excellent yields,the method displays low to moderate diastereoselectivities.…”
Section: Racemic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation